Pengembangan Permainan Ular Tangga Aktif Untuk Meningkatkan Kemampuan Kognitif Dan Kreativitas Anak Usia Dini - Ubaidillah; Agustin, Desy Rahma; Mahmudah, Siti Farihatul; Inayah, Himmatul (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to determine the feasibility of developing an active snakes and ladders game to improve the cognitive abilities and creativity of young children. The subjects in this research were early childhood children whose object was to improve cognitive abilities and creativity in children aged 5-6 years. With a sample of 15 children. This type of research is the ADDIE model which is a systematic learning design model. ADDIE is an abbreviation for Analyze, Design, Development, Implementation and Evaluation (analyze, design, develop, implement and evaluate). The data analysis technique in this research is to use data obtained from validator input at the validation stage, material experts and input from media experts. Based on the research results, from the media expert's assessment, a score was obtained with a score percentage of 98% in the "Very Good" or "Appropriate" category for use and play. The next results based on material experts obtained a score of 97.7% which was included in the "Very Good" or "Easy" category to use. And based on the results of the last validation, namely the research instrument sheet, results were also obtained at 82.9% which were in the "Easy" category to use. The validation results show that the three products are suitable for use.